2007
DOI: 10.1007/s00415-006-0297-6
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral subthalamic nucleus stimulation in advanced Parkinson’s disease

Abstract: Our data demonstrate that: 1) bilateral STN stimulation is relatively safe, improves the motor symptoms and drug-related motor complications of PD, and reduces the daily dosage of medication; 2) this benefit is sustained over time despite the occurrence of axial doparesistant signs in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…Among these studies only three reported 5-year follow-up of PD patients operated with bilateral STN stimulation [26,41,52]. Following our previous published experience [18,45], we report the results obtained 5 years postoperatively in a cohort of 42 consecutive patients with advanced PD who underwent chronic bilateral STN stimulation.…”
Section: Introductionmentioning
confidence: 97%
“…Among these studies only three reported 5-year follow-up of PD patients operated with bilateral STN stimulation [26,41,52]. Following our previous published experience [18,45], we report the results obtained 5 years postoperatively in a cohort of 42 consecutive patients with advanced PD who underwent chronic bilateral STN stimulation.…”
Section: Introductionmentioning
confidence: 97%
“…In patients insufficiently responding to, or experiencing unacceptable side effects from medical treatment, substantial and long-lasting benefits following DBS have been demonstrated, including improved motor function, reduced dyskinesia, decreased medication usage, and increased quality of life [4,5,8,11,13,16,18,19]. Patient eligibility for DBS is determined in specialised movement disorders centres using a comprehensive selection process, including a levodopa challenge test, brain imaging and assessment of neuropsychological and psychiatric functions.…”
Section: Introductionmentioning
confidence: 99%
“…Two of these studies were excluded 16,17 because the population samples were subsets of the populations in 2 other articles that were included because they had larger sample sizes. 18,19 Of the remaining 11 studies, 3 examined bilateral GPi, 9 examined bilateral STN stimulation, and 1 study included both STN and GPi target sites. 19 In the Lyons et al 20 study, 3 of the 9 subjects had unilateral GPi stimulation but the results lumped the unilateral and bilateral cases.…”
mentioning
confidence: 99%